Gastric cancer liver metastases in China: a real-world, multicentre, prospective, observational cohort study protocol - Yi Liu; Lin Chen; Hongqing Xi; Zhida Chen; Tingting Lu; Yunhe Gao; Gan Zhang; Haiya Zhang (BMJ Open)
Introduction Gastric cancer liver metastases (GCLM) is a highly heterogeneous disease with a poor prognosis. The multidisciplinary diagnosis and treatment model is applied throughout the entire treatment process. In addition to the previous RECORD study, which was based on the C-GCLM classification system developed by our team, there is a lack of recent data on patient baseline characteristics, clinical treatment and efficacy evaluation. A large-scale prospective observational study is necessary to determine the current situation of GCLM treatment in China. The findings of this study may inform the development of relevant healthcare policies, clinical pathways and treatment guidelines.Methods and analysis This is a prospective, non-interventional, observational, multicentre, real-world study designed to monitor the general condition, treatment pattern and prognosis of patients with GCLM. Patients with GCLM were classified into three distinct categories: type I (resectable type), type II (potentially resectable type) and type III (unresectable type). The patients' general information, medical history, imaging results, laboratory tests, surgical and systemic therapy details will be recorded and subjected to analysis. The 2-year overall survival (OS) will be recorded as the primary endpoint. The different therapeutic modalities employed in the treatment of GCLM, including surgery, chemotherapy and immunotherapy, will be recorded as secondary endpoints. Additionally, the effects of these therapies on prognosis, including OS of type I, II and III; R0 resection and disease-free survival of type I; and successful conversion rate and R0 resection rate and event-free survival of type II will be documented.Ethics and dissemination This study involving human participants was reviewed and approved by the Ethics Committee of Chinese PLA General Hospital (no. S2023-724-02) and will be conducted in accordance with the guidelines of the Declaration of Helsinki. Study findings will be disseminated through international peer-reviewed journal articles as well as public, academic presentations at national and international conferences.Trial registration numbers NCT06493448; ChiCTR2400083955.